Research and automation of the process of electrocoagulation wastewater treatment on the basis of the developed mathematical model - Safonyk, Andrii; Koval, Sergiy; Safonyk, Olga; Batako, Andre (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The paper presents the principles of the construction of an automated wastewater treatment system based on a generalized spatial model. A model problem, which contains descriptions of the main processes occurring in the electrocoagulation reactor taking into account the placement of the plates was developed. To verify the adequacy, a comparison between computer simulations and the results of a field experiment was made. The influence of reactor size, current density, location of electrode plates on the efficiency of chromium extraction was investigated. As a result of the study, it was proved that the mathematical model is effective for determining the parameters of the purification process, and the obtained coefficients are effective for optimizing the purification process. Based on these studies, a scheme for automation of the process of wastewater treatment from chromium was built. With the help of SCADA - WinCC, a flexible control system with the ability to control the performance of the entire installation in real time was developed.